2019
DOI: 10.3390/nano10010021
|View full text |Cite
|
Sign up to set email alerts
|

CSD-Grown Y1−xGdxBa2Cu3O7−δ-BaHfO3 Nanocomposite Films on Ni5W and IBAD Technical Substrates

Abstract: Chemical solution deposition (CSD) was used to grow Y1−xGdxBa2Cu3O7−δ-BaHfO3 (YGBCO-BHO) nanocomposite films containing 12 mol% BHO nanoparticles and various amounts of Gd, x, on two kinds of buffered metallic tapes: Ni5W and IBAD. The influence of the rare-earth stoichiometry on structure, morphology and superconducting properties of these films was studied. The growth process was carefully studied in order to find the most appropriate growth conditions for each composition and substrate. This led to a clear … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
14
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 59 publications
(81 reference statements)
0
14
0
Order By: Relevance
“…To understand the parameters that control the properties of YBCO nanocomposite films, a definitive screening design should be introduced as this is a powerful method to determine the descriptive equation of each material property with a minimal amount of experiments [55]. Further research is required to obtain homogenously distributed double-metal-oxide nanocrystals throughout the YBCO matrix with excellent superconducting properties on LaAlO 3 substrates and industrial metallic templates [56]. The critical current densities were increased by the nanocrystal addition in a wide angular range around the c-axis direction by a factor of 10 at 77 K and a factor of 7 at 30 K, whereas near the abdirection, both pristine and HfO2-YBCO films showed nearly the same values.…”
Section: Transport Measurements Of Pristine and Hfo 2 -Ybco Filmsmentioning
confidence: 99%
“…To understand the parameters that control the properties of YBCO nanocomposite films, a definitive screening design should be introduced as this is a powerful method to determine the descriptive equation of each material property with a minimal amount of experiments [55]. Further research is required to obtain homogenously distributed double-metal-oxide nanocrystals throughout the YBCO matrix with excellent superconducting properties on LaAlO 3 substrates and industrial metallic templates [56]. The critical current densities were increased by the nanocrystal addition in a wide angular range around the c-axis direction by a factor of 10 at 77 K and a factor of 7 at 30 K, whereas near the abdirection, both pristine and HfO2-YBCO films showed nearly the same values.…”
Section: Transport Measurements Of Pristine and Hfo 2 -Ybco Filmsmentioning
confidence: 99%
“…This work is a continuation of our recent publication in which we showed that YGBCO-BHO films can be grown Ni5W substrates with remarkable superconducting properties [23]. In this case we focused in study the microstructure of these films and its relationship with the critical current densities J c values obtained by transport measurements.…”
mentioning
confidence: 86%
“…Another important point besides the selection of the best superconducting film, is to use a fabrication technique that allow a transfer of the obtained results to the long-length production. It was demonstrated, in our previous work, that the use of the chemical solution deposition (CSD) is an appropriate technique for the preparation of high-quality YGBCO-BHO films on buffered metallic tapes [23]. The CSD method which is based in the use of chemical solution as precursors for the growth of the final films, is a low-cost scalable and technique that was extensively investigated in the preparation of CCs [24]- [27].…”
mentioning
confidence: 99%
“…The approach of mixing REBCO combining two or three compounds was employed multiple times in the past. 10,14–20 The improvement in the superconducting properties reported for these mixed compounds is mainly related to the distribution of the different RE 3+ ions in the matrix creating strained regions in localized areas and concomitant T c fluctuations. 14,21,22…”
Section: Introductionmentioning
confidence: 99%
“…The approach of mixing REBCO combining two or three compounds was employed multiple times in the past. 10,[14][15][16][17][18][19][20] The improvement in the superconducting properties reported for these mixed compounds is mainly related to the distribution of the different RE 3+ ions in the matrix creating strained regions in localized areas and concomitant T c uctuations. 14,21,22 In the last ve years, another step forward in the mixing strategy was taken with the appearance of the so-called High-Entropy Alloy (HEA) superconductors (for a review, see e.g.…”
Section: Introductionmentioning
confidence: 99%